Distribution of sigmodontine rodents in Northwestern Argentina: main gaps in information and new records - Jayat, Jorge Pablo (2011)
Abstract. Many uncertainties remain regarding our knowledge of sigmodontine rodent distributions in Northwestern Argentina (NWA). Most of the available information has never been critically evaluated. By reviewing the published literature and overlaying this information with other spatial layers (political, environmental, infrastructure, protected areas, and topographic layers), we identified information gaps and added new localities. The new records were obtained through field surveys, including captures and owl pellets samples. In the literature we found 561 localities, most of them published in the last decade. These records come mainly from low-altitude areas in Salta province, as well as some higher-altitude belts in Yungas, and strongly associated with roads. Records from protected areas were scarce. Akodon, Calomys, Oligoryzomys, and Phyllotis were recorded for most of the localities. We add 18 new localities for 14 species, including the first records of Akodon dolores in Tucumán province, Necromys lasiurus in Santiago del Estero and Tucumán, and Calomys lepidus in Catamarca. We add records for poorly-known species such as Andalgalomys olrogi in the Capital department (Catamarca), and Auliscomys sublimis and Neotomys ebriosus in Cochinoca (Jujuy) and La Poma (Salta). We emphasize the need for more surveys to obtain an adequate knowledge of the distribution of most sigmodontines.